Evaluation of Arabic language textbooks for the second cycle of the basic education in Sultanate of Oman in the light of the modern educational standards / Said Saif Salem al-Amri - Said Saif , Salem al-Amri (2010)
This study aims to evaluate Arabic language textbooks in the second cycle of the Basic Education, in Sultanate of Oman in the light of textbooks educational standards, and Arabic language standards. To achieve these aims, a list of textbook educational standards was set up together with a list of Arabic language standards in the second cycle of the basic education. Both lists have been approved by a panel of referees and developed into tow questionnaires. The instruments were applied to a stratified random sample of teachers and supervisors and then tested by using the (Holsti) formula for insuring the reliability. The researcher analyzed these textbooks in the light of both lists of standards by using content analysis. The study concluded that, these textbooks have taken into account the educational standards of textbooks. The textbooks standards varied between mean of (2.31-4.04). The highest mean was for the technical design, whereas the Introduction of the textbooks has the lowest rate. The researcher found the mean for these issues between (3.1-3.96). The content achieved the highest mean and the lowest was for the Introduction. Regarding to the Arabic language learning standards among the selected sample, the mean was between (3.87- 4.03). Reading standards scored the highest rate, whilst speaking standards was the lowest. However, the researcher's founding was among (4.10-4.66). Literature topics gained the highest mean and the lowest was for speaking. To sum up, this study has presented a suggestion about indicators of standards for learning the Arabic language at every class in the second cycle of Basic Education from class (5-10). In addition to that, the study concluded with a group of recommendations, however the main recommendation is the importance of implementing the educational standards in the writing of text books.